Researching tourism, leisure and hospitality for dissertations and theses - Mason, Peter (Wolvercote, Oxford Goodfellow Publishers Limited, 2022)
"Writing a dissertation can be a daunting topic - Researching Tourism, Leisure and Hospitality for Dissertations and Theses 2nd ed is a unique text that takes away the stress, worry and confusion by providing a step-by-step, user friendly guide to all you need to know to successfully research and compile your dissertation or thesis. Now in its second edition, this bestselling text has been fully revised and updated, and now includes two new chapters looking at conducting mixed methods research, as well as analysing mixed methods research.
Clearly links research processes with the presentation of these in the writing of dissertations and theses.
Draws on the work of undergraduate, postgraduate and PhD students the author has supervised, over 30 years to provide examples of dissertation/theses material.
Uses case studies/examples based on the authors own peer reviewed research.
Written in an accessible style.
Presents tried and tested student activities.
It provides a discussion of research approaches, looking at key differences and similarities. A critical evaluation of these different approaches is provided and, importantly, a discussion on selecting the appropriate approach(es) for your dissertation. It takes the reader from the initial idea and topics, through the literature review, methodology, presenting and analysing results and successfully making conclusions. Unlike other texts available, this book includes case studies based on the authors own research, as well as students work, to demonstrate different research approaches and techniques, providing an opportunity for criticism and a discussion on learning from mistakes. A must-have text for all students on how best to conduct research, compile your findings and to present them in the resulting dissertation." --
1 An Introduction to Research and Your Study -- 2 The Literature Review -- 3 Research Philosophy and Research Design -- 4 Quantitative Research Techniques and Conduct -- 5 Qualitative Research Techniques and Conduct -- 6 Mixed Methods Research -- 7 Presentation of Results -- 8 Quantitative Data Analysis -- 9 Qualitative Data Analysis -- 10 Analysing Mixed Methods Research -- 11 Conclusions -- Case Study 1.1: The role of the supervisor -- Case Study1.2: How I write -- Case Study 2.1: What to include and what to leave out in terms of the literature review. -- Case Study 2.2: Should I research my place of work? -- Case Study 2.3: Aims and objectives -- Case Study 2.4: The style of the literature review -- Case Study 3.1: Differences between positivism and constructivism -- Case Study 4.1: Student designed questionnaire: first draft -- Case Study 4.2: A representative sample? -- Case Study 5.1: Observation at Stonehenge -- Case Study 5.2: Student’s first draft of interview schedule with supervisor comments (comments in -- Case Study 5.3: Two focus groups used in connection with a music festival -- Case Study 5.4: Mountain biking focus groups, New Zealand -- Case Study 6.1: An example of mixed methods research in a Masters’ dissertation. -- Case Study 6.2: Sequential mixed methods research -- Case Study 8.1: An example of the Chi-square test -- Case Study 8.2: An example of factor analysis and ANOVA -- Case Study 9.1: Children’s understanding of the concept of a tourist -- Case Study 9.2: Observation at Wellington Zoo -- Case Study 9.3: Content analysis of a cruise ship brochure -- Case Study 9. 4: Data analysis for the qualitative phase of the Tourism Destination Quality (TDQ) study -- Case Study 9.5: Dimensions with their attributes in the TDQ study: two examples ‘Hospitable’ and 'Safe" -- Case Study 10.1: Tourism Destination Quality: Analysis of sequential exploratory mixed methods research -- Case Study 10.2: Mountain biking in New Zealand: An example of sequential explanatory mixed methods research
Includes bibliographical references and index
Keywords: Tourism -- Research -- Methodology; Hospitality industry -- Research -- Methodology; Leisure -- Research -- Methodology; Dissertations, Academic -- Authorship; Theses -- Authorship